Emissivity evaluation of human enamel and dentin - Lancaster, P. E.; Carmichael, F. A.; Clerehugh, V.; Brettle, D. S. (Frontiers in Physiology, 2022)
Background: Human enamel and dentin temperatures have been assessed with non-contact infrared imaging devices for safety and diagnostic capacity and require an emissivity parameter to enable absolute temperature measurements. Emissivity is a ratio of thermal energy emitted from an object of interest, compared to a perfect emitter at a given temperature and wavelength, being dependent on tissue composition, structure, and surface texture. Evaluating the emissivity of human enamel and dentin is varied in the literature and warrants review. The primary aim of this study was to evaluate the emissivity of the external and internal surface of human enamel and dentin, free from acquired or developmental defects, against a known reference point. The secondary aim was to assess the emissivity value of natural caries in enamel and dentin. Method: Fourteen whole human molar teeth were paired within a thermally stable chamber at 30°C. Two additional teeth (one sound and one with natural occlusal caries–ICDAS caries score 4 and radiographic score RB4) were sliced and prepared as 1-mm-thick slices and placed on a hot plate at 30°C within the chamber. A 3M Scotch Super 33 + Black Vinyl Electrical Tape was used for the known emissivity reference-point of 0.96. All samples were allowed to reach thermal equilibrium, and a FLIR SC305 infrared camera recorded the warming sequence. Emissivity values were calculated using the Tape reference point and thermal camera software. Results: The external enamel surface mean emissivity value was 0.96 (SD 0.01, 95% CI 0.96–0.97), whereas the internal enamel surface value was 0.97 (SD 0.01, 95% CI 0.96–0.98). The internal crown-dentin mean emissivity value was 0.94 (SD 0.02, 95% CI 0.92–0.95), whereas the internal root-dentin value was 0.93 (SD 0.02, 95% CI 0.91–0.94) and the surface root-dentin had a value of 0.84 (SD 0.04, 95% CI 0.77–0.91). The mean emissivity value of the internal enamel surface with caries was 0.82 (SD 0.05, 95% CI 0.38–1.25), and the value of the internal crown-dentin with caries was 0.73 (SD 0.08, 95% CI 0.54–0.92). Conclusion: The emissivity values of sound enamel, both internal and external, were similar and higher than those of all sound dentin types in this study. Sound dentin emissivity values diminished from the crown to the root and root surface. The lowest emissivity values were recorded in caries lesions of both tissues. This methodology can improve emissivity acquisition for comparison of absolute temperatures between studies which evaluate thermal safety concerns during dental procedures and may offer a caries diagnostic aid.